C0043 Ultrasound-guided ultraminimally invasive carpal tunnel release. (5th July 2018) - Villanueva, Manuel; Iborra, Alvaro; Fahandezh-Saddi, Homid; Fabian, Guillermo Rodriguez
Abstract : Background: Carpal tunnel syndrome is the most surgically treated entrapment neuropathy.Ultrasound-guided ultraminimally invasive release is performed with 1 mm incision, in an ambulant regimen, with local anaesthesia, without the need for ischemia and simultaneous bilateral release is possible even in patients with diseases considered contraindications for classic techniques. Methods: The instrument set included long needles (a 16–gauge, 1.7 mm diameter Abbocath);, a V-shaped straight curette, a blunt dissector, a hook knife (Aesculap 2, 3 mm, and an ultrasound device (Alpinion ECube15) with a 10–17MHz linear transducer. Surgical technique: The patient is placed supine, with the hand on a table and the palm up. We first try to delineate the midpoint between the nerve and the ulnar vessels, at the entry point and along the release tract through the carpal ligament, trying to define Nakamichi zone´s midpoint. We insert the small and medium V-shaped straight curette guided by the needle. We puncture 3-four times the fascia, under US control in order to facilitate the insertion of the hook-knive. We insert the hook knife following the curve of the blade so as not to enlarge the incision. The release starts 2–3 mm proximal to the superficial palmar arch, at the end of the ligament, and proximally we extend the release proximal to the pisiform. Results: We have operated on 31 hands in 20 patients, (11 bilateral cases). There were 13 women and 4 men. The Phalen test, Tinel test, reverse Phalen test, carpal compression test, and grip strength significatively improved. Two patients with residual numbness and thenar atrophy despite clinical improvement. There were no infections nor nerve damage. Conclusions: Ultrasound-guided surgery seems to be safe, helpful and successful for carpal tunnel release although some concerns remain. Ultrasound-guided, ultraminimally invasive surgery is an emerging technology that gives the surgeon direct control of the main structures. Since they can be performed on an outpatient basis under local anaesthesia and without a tourniquet, complications and contraindications are minimised. As it causes minimal pain and swelling, recovery is quicker. However, the learning curve is steep, because the surgeon has to perfect the technique with cadavers and become competent in the use of ultrasound. Large randomised controlled trials are necessary comparing this surgical technique with previous ones.